Diagnosis of Fowl Cholera in Broiler Chicken Collected from Banda Aceh and Aceh Besar - Aliza, Dwinna; Hasan, Denny Irmawati; Nazaruddin, Nazaruddin; Riady, Ginta (Jurnal Medika Veterinaria, 2024)
Fowl cholera is a highly contagious bacterial disease affecting poultry worldwide including broiler chickens. This study aimed at diagnosing fowl cholera in broiler chicken collected from Banda Aceh and Aceh Besar based on anatomical pathology and histopathological lesions. Approximately 1,400 broilers chickens cadaver were collected from poultry market around Banda Aceh and Aceh Besar within 2022-2024, then necropsied at Pathology Laboratory, Veterinary Medicine Faculty, USK. All chicken were subjected to an anatomical pathology examination, followed by histopathological observation using hematoxylin-eosin staining method. The macroscopic results revealed multifocal necrosis in the liver, hemorrhages in several internal organs, oedema in lungs, ascites in thorax cavity, and arthritis. Histopathological examination highlighted characteristic lesions including vasculitis, submucosal edema in trachea, multifocal necrosis in liver, and desquamation of intestinal villi. The prevalence rate of fowl cholera disease during 2022, 2023, and 2024 were 8,2%, 11,2%, and 14.0%, respectively. In conclusion, broilers with fowl cholera shows inflammation lesions in several organs, focal necrosis in liver, ascites in thorax and abdominal cavity in acute form, and arthritis in chronic form.